Procedure of Opinion Mining and Sentiment Analysis: A Study (International Journal of Current Engineering and Technology, 2014)
This paper covers all the essential details one must know about sentiment mining. It provides information on recent trends, applications of sentiment mining, different fields where it is used and also lot of useful information on the current research work being carried out in this area of data mining. Also, the basic workflow of the sentiment analysis process has been explained extraordinarily. Further, this paper also exemplifies the challenges and the future research being planned in the field of sentiment and opinion mining.
Keywords: Data Mining; Data Pre-processing; Analysis; Opinion; Tweets